Can Incomplete Metastasectomy Impact Renal Cell Carcinoma Outcomes? A Propensity Score Matching Analysis From a Prospective Multicenter Collaboration - Alice Dragomir, Charles Hesswani, Gautier Marcq, Alan I So, Christian Kollmannsberger, Naveen S. Basappa, Adrian Fairey, Anil Kapoor, Aly-Khan A. Lalani, Antonio Finelli, Lori A Wood, Daniel Y.C. Heng, Georg Bjarnason, Rodney H. Breau, Luke T. Lavallée, Denis Soulières, Darrel Drachenberg, Frédéric Pouliot, Simon Tanguay (Société Internationale d’Urologie Journal)
ObjectivesTo evaluate the role of incomplete metastasectomy (IM) for patients with metastatic renal cell carcinoma (mRCC) on overall survival (OS) and time to introduction of first-line systemic therapy. MethodsPatients diagnosed with mRCC between January 2011 and April 2019 in 16 centers were selected from the Canadian Kidney Cancer information system database. We included mRCC patients who had prior nephrectomy and had received an IM (resection of at least 1 metastasis) or no metastasectomy (NM). A propensity score matching was performed to minimize selection bias. Cox proportional hazards analysis was used to assess the impact of the metastasectomy while adjusting for potential confounders. OS was assessed by Kaplan-Meier analysis. ResultsA total of 138 patients with mRCC underwent IM, while 1221 patients did not. On multivariate analysis, IM did not improve OS (hazard ratio [HR] 0.96, 95% CI 0.63 to 1.45, P = 0.836) However, subgroup analyses revealed IM improved OS compared with NM when lungs were the only site involved (median time to OS not reached versus 66 months, respectively; P = 0.014). Additionally, lung metastasectomy delayed the systemic therapy compared with NM (median 41 and 13 months, respectively, P = 0.014). IM of endocrine organs (thyroid, pancreas, adrenals) or bone metastases did not impact OS. ConclusionThe role of IM for mRCC is limited. Incomplete resection of lung metastases was associated with improved OS and delayed time to introduction of systemic therapy when lungs were the sole location of metastatic disease. Despite case-matching, unknown unadjusted confounders may explain the relationship between IM and survival in this analysis.